IMPLEMENTASI PENCATATAN KEUANGAN PADA USAHA KECIL DAN MENENGAH : Studi pada Toko Kelontong di Kecamatan Panjang - Lestari, Dwi; Maulina, Mila (LP2M Universitas Bina Bangsa, 2024)
Research The studi aims to find out the application of daily financial record to existing Small and Medium Micro Enterprises (UMKM) units in Long-Term Sub-district, with data analysis techniques using qualitative descriptive analysis techniques. The data collected was obtained through interviews with sources to see the implementation of the implemented daily financial record. From the research results, it is known that grocery stores in long sub-districts that are the object of the study did not do their detailed financial records at all. The owner only relies on the memory of managing the finances on his business